Literatürden Edebiyata - Yılmaz, Durali (İstanbul Kültür Üniversitesi Yayınları, 2003)
Batılılaşma sürecinde dilimize giren kavramlar; bazen olduğu gibi, bazen de çeviri olarak geliyordu Bu da bir kavram kargaşasına neden oluyordu. 'Literatür'ü Türkçe 'yazın' kavramı yerine edep anlamını içeren 'edebiyat ile karşılayınca; Yeni Türk Edebiyatı, ahlak kurallarına uygun, öğretici ve eğitici olarak doğdu ve bu anlayışa uymayan çalışmalar, edebiyat dışı sayıldı. Concepts that were imported from other languages during the Westernization process, sometimes were used as non-translations in the Turkish polysystem and sometimes were translated into Turkish. This, therefore, caused a conceptuel confusion. For example, the concept pf 'literature' (literatür) was translated into Turkish as 'edebiyat' instead of 'yazın'. However, as the concept 'edebiyat' stems from the term 'edep', which has moral connotations, Modern Turkish Literature set out to be morally acceptable and didactic, and everything written that did not fit into this perception was not regarded as literature.
Keywords: Edebiyat; Edep; Kavram; literature; decorum; notion